Implementing Indonesia's Free Health Check National Priority Program: A Case Study of Saka Kajang Village, Pulang Pisau Regency - Suprayitno; Mochammad Helmy Fikri; Trisni Salsa Ramadina; Peronika Simanjuntak; Cyntia Lupita Sari; Melia Sintha (Jurnal Administrasi dan Kebijakan Publik, 2026)
The Cek Kesehatan Gratis (CKG) program is one of Indonesia's national priority initiatives designed to improve equitable access to preventive healthcare services. This study aims to analyze the implementation of the CKG program in Saka Kajang Village, Pulang Pisau Regency, Central Kalimantan Province. A qualitative descriptive approach was employed to obtain an in-depth understanding of the program's implementation. Data were collected through in-depth interviews with key stakeholders, field observations, and a review of relevant documents and literature. The findings indicate that the program has generally been implemented effectively and has been positively received by the local community because it improves access to free health screening services. Despite these achievements, several challenges remain, including limited healthcare facilities, inadequate financial and human resources, and the need for stronger coordination among implementing agencies. These constraints may affect the consistency and sustainability of program implementation if not adequately addressed. The study concludes that strengthening institutional coordination, improving resource allocation, and maintaining government commitment are essential to enhance the effectiveness and long-term sustainability of the CKG program. These findings provide practical implications for local governments, policymakers, and researchers seeking to strengthen the implementation of preventive healthcare policies in Indonesia.